2011
DOI: 10.1016/j.jval.2011.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Gastos do Ministério da Saúde do Brasil com Medicamentos de Alto Custo: Uma Análise Centrada no Paciente

Abstract: The understanding of the expenses involved subsidizes restructuring actions and scheduling drug programs, also provides information for therapeutic groups which are priorities for analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
0
12
0
10
Order By: Relevance
“…Another limitation is the potential duplication of patients' records within DATASUS databases; considering evidence showing that quality of data extracted from DATASUS may be compromised due to duplication or lack of consistency in the patients' registry, depending on the type of information used 18,19 . Nevertheless, with regard to the CEAF data, limitations are considerably lower, due to the need of medical prescriptions for treatment of each patient diagnosed within the SUS during the same period (monthly).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the potential duplication of patients' records within DATASUS databases; considering evidence showing that quality of data extracted from DATASUS may be compromised due to duplication or lack of consistency in the patients' registry, depending on the type of information used 18,19 . Nevertheless, with regard to the CEAF data, limitations are considerably lower, due to the need of medical prescriptions for treatment of each patient diagnosed within the SUS during the same period (monthly).…”
Section: Discussionmentioning
confidence: 99%
“…Cushing syndrome accounts for 510 cases/million/year (44) and celiac disease has a prevalence of 1% (45 Direct costs related to the management of osteoporosis: treatment It is estimated that SUS accounts for the provision of healthcare to 75.5% of the Brazilian citizens, and medications represent a sizable fraction of the public spending with health (47). The expenses of Brazil's Ministry of Health with drugs acting on bone struc ture and mineralization correspond to approximately 10.9% of the total spending with highcost medications (48). In the São Paulo public health system, in 1998, the mean annual cost for postmenopausal osteoporo sis treatment in ambulatory patients amounted to 775 dollars per patient, and outofthepocket payments by the patients corresponded to 9% of the monthly family income (49).…”
Section: Direct Costs Related To the Management Of Osteoporosis: The mentioning
confidence: 99%
“…For instance, a study carried out in the state of Rio de Janeiro, Brazil, found that most antimicrobial costs came from primary rather than hospital care. (5) The non-hospital environment in Brazil does not have a specific surveillance system on the rational use of drugs, including antimicrobials, which limits monitoring and controlling this drug, and favors its empirically exacerbated use. In addition, an irregular and non-directed distribution can lead to AMR and potentiate unnecessary expenses.…”
Section: Introductionmentioning
confidence: 99%